PERAN CORE EVALUATIONS TERHADAP KEPUASAN KERJA DAN PSYCHOLOGICAL WELL-BEING (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2009)
This research is in order to empiricaly testing about role of core evaluations against job satisfaction and psychological well-being. Core evaluations are individual dispotitions influence on the individual evaluate it self and environment. Core evaluations consist of five dimentions, locus of control, self-esteem, self-efficacy, neurotism, and edternal core evaluations, which be presumed contribute to the job satisfaction and psychological well-being. This research derivation is carry out by the using of scale in the form of questionnaire. Use 75 employess company in Jogjakarta as respondent, this research conclude that core evaluations leading role to job satisfaction amount of 15,7% and d3,3% to psychological well-being